PENGEMBANGAN SISTEM JARINGAN DISTRIBUSI AIE BERSIH DI KECAMATAN TUREN. - Ali, Moh. Abdullah (Media Teknik Sipil, 2011)
The population growth and district expansion needs supplying of clean water to fullfill thebasic requirements for the citizens, even from the quantity and quality. The distribution networksystem in that area using gravitation with heterogen pipe. The control to debite and pressure usedas parameter the operation of network service to the customer needs of clean water.Existing ( 2008 ) the population was 50237 people, with the growth average on 0,2percen each year. The needs of clean water at 23,8 lt/dt at the top of condition on the 60 percenservice level. From the analyst known that for the population at 2019 wich accounted by Geometricmethode was at 65,344 people. The clean water needs 106,4 lt/dt at the top of condition on 80percen service level.The plan for developing distribution network system, network simplication to minimizeof over network and to decrease the reducer cause of pipe curve at the existing network. Thenetwork pipe at Turen area needs increasing pipe on the existing condition 255 pipes with increasingto be 300 pipes. Node from the existing condition 251 node with increasing to be 287 node. Theresult of software WaterNet simulation is the dimension of network pipe for 2019. The dimensionof distribution pipe network before developing from the resouce to the customer are 250 mm, 200mm, 160 mm, 110 mm, 90 mm, 63 mm, and 40 mm. While the dimension of distribution pipenetwork after developing are 355 mm, 315 mm, 250 mm, 200 mm, 160 mm, 110 mm, 90 mm, 63mm, and 40 mm.Keyword : Network pipe system, Water needs, Developing